Proton reconstruction with the CMS-TOTEM Precision Proton Spectrometer - Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Damanakis,K; Dragicevic,M; Del,Valle AE; Hussain,PS; Jeitler,M; Krammer,N; Lechner,L; et al. (Journal of Instrumentation, 2023)
The Precision Proton Spectrometer (PPS) of the CMS and TOTEM experiments col-lected 107.7 fb1 in proton-proton (pp) collisions at the LHC at 13 TeV (Run 2). This paper describesthe key features of the PPS alignment and optics calibrations, the proton reconstruction procedure,as well as the detector efficiency and the performance of the PPS simulation. The reconstructionand simulation are validated using a sample of (semi)exclusive dilepton events. The performanceof PPS has proven the feasibility of continuously operating a near-beam proton spectrometer at ahigh luminosity hadron collider.